O jargão LGBTQ em Rupaul's Drag Race traduzido e legendado por fãs: um estudo baseado em corpus - Braga Junior, Sebastião Jairo Lima (2020)
This dissertation addresses fansubbing in the ninth season of the Reality Show RuPaul’s Drag Race (RPDR), based on Corpus Linguistics tools. The objective was to reflect on the cultural representation of LGBTQ + slang in the reality show subtitles, drawing a parallelism between the North American and Brazilian LGBTQ + slang. The focus of the study is the occurrences of terms translated in unexpected contexts, having as reference the technical standards of subtitling, an electronic dictionary (Linguee), and the LGBTQ Aurélia dictionary, a study by Scippe and Libi (2006). At first, the subtitles were made available by the Fabutrash group in Portuguese and English; then, the LGBTQ + slang was labeled in its source language (English) and in the target language (Portuguese) in “txt” format. The alignment of both translations and the wordlist tool guided the lexical items of the jargon to be searched. The occurrences were analyzed using the Lancsbox software, which in turn made it possible to organize the tables for analysis, the data were interpreted taking into account the context (episode) in which they are inserted and the translation choices made by the fan translators (fansubbers), the Antconc software was used for checking. The translations were compared with those available in an electronic dictionary to validate the findings, as well as to highlight the importance of including such terms based on the frequency of occurrence. This study is based on Cintas and Remael's (2007) subtitling vision, and correlates contributions from Venuti (2002), Tarallo (1986), Sinclair (2005) and Calvet (2001), which highlights the interdisciplinarity in Translation Studies, as well as the contributions of Brennan and Gudelunas (2017) to RPDR studies.